Model Pelatihan Penyusunan Perangkat Pembelajaran untuk Meningkatkan Kompetensi Guru Bahasa Jawa SMP di Kabupaten Karanganyar - Favorita Kurwidaria; S. Sumarwati; Nugraheni Eko Wardani (Jurnal VARIDIKA, 2019)
n supporting the achievement of learning objectives, teachers need to be able to arrange learning tools in accordance with the applicable curriculum. The learning device functions as a guide in carrying out the learning process in the classroom. Javanese language teachers in SMP in Karanganyar Regency, in general, have been aware of the importance of renewal in developing and implementing learning tools, in accordance with the applicable curriculum. However, in reality there are still many teachers who do not understand, even still find it difficult to arrange learning tools, so there are still inaccuracies in the learning tools. Training on the preparation of learning tools for Javanese junior high school teachers, especially in Karanganyar Regency based on the applicable curriculum, was felt to be necessary. To support the effectiveness of training activities, it is necessary to innovate in its implementation. One model that can be applied is the tutorial model, with peer tutors and providing feedback. The purpose of implementing the activity by applying the model is that teachers can exchange knowledge, experience, and strengthen cooperation between peers, so that they can provide input and correction if there is inaccuracy. In addition, through giving feedback teachers can find out firsthand the deficiencies in the learning implementation plan that they put together. After applying these methods the ability of Javanese junior high school language teachers in developing learning tools in accordance with the curriculum can be increased. This can be seen from the results of the lesson plans that have been revised by the training participants.